Optic Neuropathy Secondary to Polyarteritis Nodosa, Case Report, and Diagnostic Challenges - Vazquez-Romo, Kristian A.; Rodriguez-Hernandez, Adrian; Paczka, Jose A.; Nuño-Suarez, Moises A.; Rocha-Muñoz, Alberto D.; Zavala-Cerna, Maria G. (Frontiers in Neurology, 2017)
Purpose: To describe a case of optic neuropathy as a primary manifestation of polyarteritis nodosa (PAN), and discuss diagnostic challenges. Methods: Case report. Results: A 41-year-old Hispanic man presented with a two-day history of reduced visual acuity in his left eye. Physical examination revealed a complete visual field loss in the affected eye. Best-corrected visual acuity (BCVA) in the left eye was hand motion, and fundus examination revealed a hyperemic optic disc with blurred margins, swelling, retinal folds, dilated veins, and normal size arteries. BCVA in the right eye was 20/20; no anomalies were seen during examination of the fundus. The patient was started on oral corticosteroids and once the diagnosis of PAN was made, cyclophosphamide was added to the treatment regimen. Six months later, the patient recovered his BCVA to 20/20 in his left eye. Conclusions: Rarely does optic neuropathy present as a primary manifestation of PAN, nevertheless it represents an ophthalmologic emergency that requires expeditious anti-inflammatory and immunosuppressive treatment to decrease the probability of permanent visual damage. Unfortunately, diagnosing PAN is challenging as it necessitates a high index of suspicion. In young male patients that present for the first time with diminished visual acuity, ophthalmologist become cornerstones in the suspicion of this diagnosis and should be responsible for continuing the study until a diagnosis is reached to ensure rapid commencement of immunosuppressive treatment.